Mining the Short Side: Institutional Investors and Stock Market Anomalies - Gao, Xin; Wang, Ying (Journal of Financial and Quantitative Analysis, 2023)
This article investigates the short-side anomaly trading behavior of alternative mutual funds (AMFs) based on their short positions in U.S. domestic equities. In aggregate, AMFs demonstrate the ability to exploit well-documented stock market anomalies on the short side, and the overpriced stocks sold short by AMFs generate significant negative alpha. Further, AMFs’ short-side trades exhibit significant return predictability, which can at least partially derive from their ability to process public information on firm and anomaly characteristics. Finally, AMFs’ short-side anomaly-based trading activity and profitability appear to be more pronounced among the stocks with higher credit risk or dynamic short-selling risk.